Wind effects on young coffee plants 'Mundo Novo' and 'Catuaí Vermelho' - Caramori, Paulo Henrique; Ometto, José Carlos; Nova, Nilson Augusto; Costa, José Dias (Pesquisa Agropecuaria Brasileira, 2014)
Young coffee (Coffea arabica L.) plants, cultivars Mundo Novo LCMP 376-4 and Catuaí Vermelho H 2077-2-5-81 grown under nursery conditions were exposed to mean wind speeds of 1, 2 and 3 m.s-1and were compared with seedlings under natural nursery conditions, where the mean wind speed was 0.08 m.s-1. The experiment was carried out in 40 days, and estimations were made of growth, water consumption and mechanical damage. The main results obtained were: 1. Less increase in plant height, length of internodes, number and length of plagiotropic branches, dry matter weight, leaf area, net assimilation rate and relative growth rate starting from mean wind speed of 2 m.s-1. 2. For the plants exposed to wind speeds of 1 and 2 m.s-1 the cultivar Catuaí presented higher transpiration rate greater dry matter weight and higher net assimilation rate, probably because the evaporative demand was met to a greater extent. 3. Mechanical damage was stressed by the increase in wind speed, becoming severe in plants exposed to 2 and 3 m.s-1.